2021
DOI: 10.1007/s00520-021-06354-y
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of returning to work following treatment and the associated personal, disease, and treatment factors among breast cancer survivors in central China

Abstract: Purpose To assess the status of returning to work (RTW) following breast cancer treatment and to explore its associated factors among female patients. Methods Four-hundred-forty-two eligible patients admitted in a tertiary hospital since 2012 were followed up in 2018. Information about working status after treatment, date of RTW or reason for not RTW was obtained during a 30-min interview. Patients’ sociodemographic, disease, and treatment characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…A similar RTW rate was found by Li et al in a retrospective cohort study among 396 BCS. The overall RTW rates at 12 and 36 months following cancer treatment were 24.4% and 32.7%, respectively [10]. BCS face similar workplace challenges in China to those observed in other countries [11].…”
Section: Introductionmentioning
confidence: 82%
“…A similar RTW rate was found by Li et al in a retrospective cohort study among 396 BCS. The overall RTW rates at 12 and 36 months following cancer treatment were 24.4% and 32.7%, respectively [10]. BCS face similar workplace challenges in China to those observed in other countries [11].…”
Section: Introductionmentioning
confidence: 82%
“…La fatiga prolongada es uno de los factores que afecta el desempeño en el trabajo. Nuestros datos muestran que una alta proporción de mujeres supervivientes de cáncer de mama refiere astenia, superando cifras de mujeres en China (45) y en Israel (35). Un 32% de las pacientes con esta secuela, perciben un bajo apoyo organizacional, que sería fundamental para lograr un retorno laboral sostenido de estas pacientes (46, 47).…”
Section: Discussionunclassified
“…Multiple factors are associated with the probability of RTW. Many studies [ 11 , 12 ] have reported that younger age, higher education level, single status, high income and good employer support are associated with higher levels of RTW. On the other hand, old age, low education level, low income and poor support were barriers to RTW.…”
Section: Discussionmentioning
confidence: 99%